Analisis Pengaruh Ekspor, Investasi dan Tenaga Kerja Terhadap GDP Indonesia Tahun 1990-2020 - Afifatus, Lutfi (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
This research was conducted with the aim of analyzing the effect of oil and gas exports, non-oil exports, investment and labor on Indonesia's economic growth. The data used in this study is time series data with a time span from 1990 to 2020 using the ECM (Error Correction Model) data analysis method with the help of Eviews10 software. In this study, it was found that the Oil and Gas Export Variable variable did not have a significant effect on GDP in Indonesia both in the long and short term while the Non Oil and Gas Export variable had a significant effect on Indonesia's GDP in the long term but did not have a significant effect in the long term. short. Investment variable has a significant influence on GDP in Indonesia, both in the long term and in the short term and for the Labor variable has a significant influence on GDP in Indonesia in the long term, but in the short term the Labor variable does not have a significant effect on Indonesia's GDP